Cambios en la vía aérea en pacientes ortodónticos con cirugía ortognática, revisión de alcance (2024)
Orthognathic surgery is a key intervention for correcting dentofacial deformities. In addition to its aesthetic benefits, it generates significant postoperative changes in the upper airways. Various studies have shown that procedures such as mandibular or maxillomandibular advancement not only improve skeletal alignment but also lead to a significant increase in the volume of the oropharynx and nasopharynx, which can enhance respiratory function, particularly in patients with obstructive sleep apnea.